2016
DOI: 10.1007/s10571-016-0445-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Preconditioning Augments the Therapeutic Efficacy of Bone Marrow Stromal Cells in a Rat Ischemic Stroke Model

Abstract: Transplantation of bone marrow stromal cells (BMSCs) is a promising therapy for ischemic stroke, but the poor oxygen environment in brain lesions limits the efficacy of cell-based therapies. Here, we tested whether hypoxic preconditioning (HP) could augment the efficacy of BMSC transplantation in a rat ischemic stroke model and investigated the underlying mechanism of the effect of HP. In vitro, BMSCs were divided into five passage (P0, P1, P2, P3, and P4) groups, and HP was applied to the groups by incubating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 54 publications
4
47
0
Order By: Relevance
“…Various pathological mechanisms are involved in the pathogenesis of ischemic brain injury and exert complex interaction effects. Recent studies in rodents have shown that cell apoptosis is significantly increased in 24–72 hr, and this effect lasts up to 7 days after ischemia (J. Chen et al, ; Liu et al, ; Lv et al, ; Y. Sun et al, ), which indicates that apoptosis may be an important mechanism underlying ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Various pathological mechanisms are involved in the pathogenesis of ischemic brain injury and exert complex interaction effects. Recent studies in rodents have shown that cell apoptosis is significantly increased in 24–72 hr, and this effect lasts up to 7 days after ischemia (J. Chen et al, ; Liu et al, ; Lv et al, ; Y. Sun et al, ), which indicates that apoptosis may be an important mechanism underlying ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe that BMSCs may promote bone repair up to 5 months. Rosová et al [ 40 ] and Chen et al [ 41 ] reported that hypoxic conditions could improve BMSC survival and tissue regenerative potential in vivo , and the Matrigel hydrogel microenvironment is moderately hypoxic. Similarly, in our scaffold + Matrigel group, Matrigel without BMSCs inside only formed new bone on the surface of the scaffold, not inside (Figures 7(g) and 8(g) ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that hypoxic preconditioning increases tolerance to hypoxic-ischemic-induced brain injury and decreases apoptosis by upregulating the expression of HIF-1α (14). Furthermore, hypoxic preconditioning in transplanted bone marrow stromal cells promoted their capability of regeneration and therapeutic potential to treat rat ischemic stroke (15).…”
Section: Introductionmentioning
confidence: 99%